A comparative study of vascular epiphytes in three epiphyte rich habitats at Ulu Endau Johore Malaysia - Kiew, Ruth; Anthonysamy, S. (Malaysian Nature Society, 1987)
A survey of epiphytes was carried out in three habitats where epiphytes were conspicuous, viz on a sandy island, in swampy heath forest and on Machaerina bog. In total 44 epiphyte species were recorded, about half the species were dicotyledons, the remainder were orchids and ferns in almost equal numbers. The island supported twice the number of species (33) as the other two habitats (14 and 11). Only four species were common to all three sites. The most common epiphyte species were associated with ants. These included classic ant-plants (Hydnophytum formicarium and Dischidia major) and epiphytes the germinate and grow in ant's nests and runways forming anti-gardens, a phenomenon not previously reported from Asia. The number of epiphytes per tree was low ranging from 1-4 on trees in Machaerina bog to 2-11 on trees on the island. Epiphyte abundance was not related to bark type but larger (presumably older) trees of the same species carried more epiphytes than smaller trees. On the Machaerina bog, a higher proportion of Gluta aptera trees supported epiphytes than other tree species probably because and nests were more frequent on this tree species.